Complementary diagnosis of the genus Insuetophrynus (Anura, Cycloramphidae) based on larval characters - Rabanal, Felipe E.; Formas, J. Ramon (Zootaxa, 2009)
The external and internal characteristics of the tadpoles of Insuetophrynus acarpicus are compared with other members of the family Cycloramphidae and used to complement the generic diagnosis previously based solely on adult morphological characteristics. The redescription includes larval external morphology, internal buccal features examined by SEM, and description of the chondrocranium and hyobranchial apparatus.